THE BARRIERS THAT HINDER THE ADOPTION OF ECOMMERCE BY SMALL BUSINESSES IN PALESTINE - Ahmed A.M.Abualrob (Graduate School of International Studies Ajou University, 2014)
ABSTRACT E-commerce is an international trend to conduct online business through internet. It is one of the most effective tools for enhancing business activities owing to its flexibility and high efficiency to increase productivity. Palestine one of the developing countries that has realized the benefits of e-commerce recently due to several barriers that affect the adoption of ecommerce there. This study, will attempt to highlight the major barriers that hinder the adoption of EC in Palestine using TOE framework (Tornatzky et al. 1990), and the model of innovation resistance by Ram (1987), and other related theories such as (DOI). Likewise, an online survey has conducted to collect data from around 161-business owners in Palestine; and the model has tested by using structural equation modeling (SEM) to analyze the survey respondents, (SEM) has employed to examine the inter-correlations among the proposed constructs. Moreover confirmatory factor analysis has used to determine the measurement efficacies. The analysis has conducted by using SPSS and SmartPLS tools. The study has tackled specifically the Political instability, Israeli occupation restrictions that have been imposed on several sectors in Palestine and the unreliable logistics services, in addition to business’s owner behavior factors such as perceived losses, uncertainty and complexity. Palestine has failed to develop its own ecommerce system due to the barriers stated above. This paper mainly focuses on the barriers that prevent the adoption of ecommerce by small businesses in Palestine.
학위논문(석사)--아주대학교 국제대학원 :국제경영학과,2014. 8
Keywords: e-Commerce Barriers; e-Commerce Adoption; Small Businesses; Israeli Occupation; Palestine